Adequacy of Prenatal Care Between Hospital-Based, Prepaid, Bundled Program and Traditional Medicaid [28C]. (May 2018) - Duncan, Erin; Narvaez, Jennifer; Topel, Matthew; Haddad, Lisa; Loucks, Tammy; Ellis, Jane
Abstract : INTRODUCTION: Access to adequate prenatal care (PNC) is a goal of HealthyPeople 2020. However, not all pregnancies in the U.S. are guaranteed this benefit, particularly in States that have not expanded Medicaid or have high concentrations of pregnancies in undocumented women. To address this gap, our institution created a prepaid, bundled PNC package (Grady Healthy Baby-GHB) for women who did not qualify for public insurance. Prenatal visits and two ultrasounds were included. Our goal was to determine whether GHB participants received adequate PNC relative to Medicaid. METHODS: Viable singleton deliveries from 2011-2014 were eligible. A randomly selected, retrospective cohort of 100 GHB and 100 Medicaid deliveries was created. Demographics, pregnancy information, number of prenatal visits and ultrasounds were abstracted and pregnancy risk status and adequacy of PNC determined. Descriptive statistics and logistic regression models were used to characterize groups and examine adequacy of PNC. RESULTS: GHB participants were older, more likely to be Hispanic and less likely to be Black compared to Medicaid participants (P<0.001 for all). Among women with a low risk pregnancy, GHB participants were more likely to have adequate PNC compared to Medicaid patients (P<0.001). Significance remained after adjustment (aOR 3.75, P=0.015). In high risk pregnancies, there was no difference in adequacy of PNC. CONCLUSION: Women with low risk pregnancies enrolled in a prepaid, bundled PNC package were more likely to receive adequate care than women with Medicaid. This study has implications for all pregnancies that begin as uninsured, especially in the current political climate.